2018
DOI: 10.1002/jsfa.9097
|View full text |Cite
|
Sign up to set email alerts
|

Gold lotion from citrus peel extract ameliorates imiquimod‐induced psoriasis‐like dermatitis in murine

Abstract: Our results indicate GL can act to suppress the initiation of psoriasis and strongly suggest that GL may have potential to be applied to the treatment of psoriasis. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…We also confirmed previously achieved results concerning the potential use of a new, natural, and non-corrosive sanitizing product (GL) to achieve significant bactericidal effect against all tested bacterial strains [29,42]. In particular, GL is rich in flavonoids, which are natural compounds that have been extensively studied for their antibacterial properties [29,[43][44][45], and can be considered a valuable alternative candidate to commercially available sanitizing products for stainless steel such as iodine, biguanide, quaternary ammonium compounds, peracetic acid and sodium hypochlorite that showed evident corrosive action [46].…”
Section: Discussionsupporting
confidence: 88%
“…We also confirmed previously achieved results concerning the potential use of a new, natural, and non-corrosive sanitizing product (GL) to achieve significant bactericidal effect against all tested bacterial strains [29,42]. In particular, GL is rich in flavonoids, which are natural compounds that have been extensively studied for their antibacterial properties [29,[43][44][45], and can be considered a valuable alternative candidate to commercially available sanitizing products for stainless steel such as iodine, biguanide, quaternary ammonium compounds, peracetic acid and sodium hypochlorite that showed evident corrosive action [46].…”
Section: Discussionsupporting
confidence: 88%
“…Various components of citrus peel extract (CPE) are also suggested to exert inhibitory effects in skin aging through diverse mechanisms including inhibition of collagenase activity, induction of procollagen synthesis, and anti-inflammatory activity. 10 -12 However, little information is available about the inhibition of melanogenesis by citrus peel. The purpose of this study was to investigate the inhibitory effect of CPE on tyrosinase enzyme and melanin synthesis in murine melanocytes and to research whether oral intake of CPE exerts a useful effect on skin brightening in vivo model.…”
mentioning
confidence: 99%
“…9,10 3,3′,4′,5,6,7,8-Heptamethoxyflavone (HMF) that makes up polymethoxy-flavonoids with tangeretin and nobiletin is a major ingredient of citrus peel and has anti-inflammatory activity as well as antioxidant activity. 7,11 β-Cryptoxanthin is one of the 6 major carotenoids found in human blood, in addition to a-carotene, b-carotene, lutein, zeaxanthin, and lycopene. It was revealed that β-cryptoxanthin has preventive effects against osteoporosis, diabetes, arteriosclerosis, and liver malfunction and also has antioxidant activity, anticancer activity, and stimulatory effects on the immune system.…”
mentioning
confidence: 99%
“…Gold lotion, an ethanolic extract of a mixture from peels of six citrus fruits, including Citrus sinensis (navel oranges), Citrus hassaku, Citrus limon, Citrus natsudaidai, Citrus miyauchi Iyo, and Citrus unshiu (Satsuma) decreased the ratio of Th17 cells in the spleen and reduced the expression of IL-23, IL-6, TNF-α, IL-17, and IL-22 at mRNA levels in skin lesions in IMQ-induced mouse model of psoriasis [39]. Bai Xuan Xia Ta Re Pian, a traditional herbal formula consisting of six herbs (Euphorbia Humifusae Herba, Chebula Fructus, Terminalia bellirica Fructus, Chebula Fructus Immaturus, Aloe, and Resina Scammoniae) significantly suppressed the expression of IL-23 and IL-17 in the skin of psoriatic mice [40].…”
Section: Classical Signaling Pathwaysmentioning
confidence: 99%